The Evaluation of Cellular Immunity to Avian Viral Diseases: Methods, Applications, and Challenges - Hao, Xiaoli; Zhang, Fan; Yang, Yi; Shang, Shaobin (Frontiers in Microbiology, 2021)
Cellular immune responses play critical roles in the control of viral infection. However, the immune protection against avian viral diseases (AVDs), a major challenge to poultry industry, is yet mainly evaluated by measuring humoral immune response though antibody-independent immune protection was increasingly evident in the development of vaccines against some of these diseases. The evaluation of cellular immune response to avian viral infection has long been neglected due to limited reagents and methods. Recently, with the availability of more immunological reagents and validated approaches, the evaluation of cellular immunity has become feasible and necessary for AVD. Herein, we reviewed the methods used for evaluating T cell immunity in chickens following infection or vaccination, which are involved in the definition of different cellular subset, the analysis of T cell activation, proliferation and cytokine secretion, and in vitro culture of antigen-presenting cells (APC) and T cells. The pros and cons of each method were discussed, and potential future directions to enhance the studies of avian cellular immunity were suggested. The methodological improvement and standardization in analyzing cellular immune response in birds after viral infection or vaccination would facilitate the dissection of mechanism of immune protection and the development of novel vaccines and therapeutics against AVD.